A Conversation with Laura Ellen Bacon. (2nd September 2017) - Chandler, Kimberley; Knott, Stephen
Abstract: This interview explores the work of Laura Ellen Bacon, and focuses on her recent exploration of thatch for an exhibition at the National Centre of Craft and Design in Sleaford, UK. Primarily known for her work in willow—on show in the current Woman's Hour Craft Prize exhibition (BBC Radio 4/Crafts Council/Victoria & Albert Museum)—this interview centers on Bacon's response to a new material, its processes and traditions. Questions of material knowledge, learned skill, dexterity, and intuition emerge, as well as the comparative qualities of willow and thatch: the former, a pliant material commonly used in basketry; and the latter, bundles of wheat straw, reeds, or heather that are not woven or tied, but rather arranged in layers to form a protective roof covering.